Analisis Kinerja Petugas Dalam Melakukan Pelayanan Rawat Jalan di Puskesmas Kalisat - Novia Zahroh; Indah Muflihatin (Politeknik Negeri Jember, 2020)
Performance is the result of quality and quantity of work accomplished by each employee based on the jobdescription or responsibility. The standard of a good performance are at least precision, intelligence, quickness, and orderliness. Kalisat Public health center has a problem which is underoptimal performance in providing service to patients so that affecting to the pastientâ€™s satisfaction. This research was aimed to analyze employeeâ€™s performance within outpatient service in Kalisat Public health center Jember district. The method is analityc observational cross sectional design as the research method. There were 20 employees in outpatient service as the research sample obtained by saturated sampling. It was analyzed by applying the data tabulation software. This result showed that most of the employees were average in their good motivation (60%), they were good at the oppurtunity (50%),they were good at the ability (55%), and the performance of outpatient service belongs to a good category (50%). It shows that there were significant relationship between motivation, oppurtunity, ability, and performance of outpatient employees with significancy value < 0,05 and Â X2 value > X2 table. The improvement efforts can be made by developing information system, division of labor improvement, good delegation of competency, and increasing training.